Childhood psoriasis: What is new and what is news - Sunil Dogra; Anuradha Bishnoi (Wolters Kluwer Medknow Publications, 2018)
Psoriasis is a chronic inflammatory disorder that affects around 2%-4% of the general population, and the prevalence can be higher in selected populations. About one-third of the people affected with psoriasis have the onset of their disease in the first and second decades of life. Of the pediatric population, about 0.5%-2% is affected. Infants are affected rarely. The incidence increases with age and is reported to be ~0.55% in the age group of 0-9 years and 1.37% in the age group of 10-19 years. Flexures, face, periauricular area and medial aspect of the upper eyelid are commonly involved in children. In infants, there is predilection for diaper area. Overall, plaque psoriasis is the most common type, followed by guttate and pustular psoriasis. Lesions are more pruritic, but thinner, less erythematous, and less scaly. Follicular lesions are common. Treating psoriatic erythroderma can pose difficulties, especially in pediatric population. Some cases achieve rapid control of disease activity, while others develop chronic erythroderma with frequent disease flares. The impact of disease on psychosocial parameters is significant in this subgroup of psoriasis and affects patients and parents alike with significantly high rates of absenteeism from school. Pediatric psoriasis therefore needs to be managed effectively. However, effective treatment also poses the risk of producing adverse effects, more so in pediatric age group. A delicate balance therefore should be maintained and overzealous treatment should be avoided.